Myth and Post-Apartheid Socio-Economic Challenges in Zakes Mda’s The Heart of Redness - Ojedoja, Sanjo (IJRDO - Journal of Social Science and Humanities Research, 2018)
This paper has identified the conflict between modern life and urban civilization and a valued history by revealing the challenges of post-colonial identity which includes the relationship between personal and cultural identity and such issues as double consciousness and hybridity. This paper will examine how Mda in The Heart of Redness delves into the mythical past and its divide to deftly portray the current socio-economic challenges posed to South African society. This paper shall adopt postcolonial theory.